2017
DOI: 10.1371/journal.pone.0175867
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden for patients with primary immunodeficiency diseases identified at reference hospitals in Guanajuato, Mexico

Abstract: BackgroundIn addition to the deleterious effect on health, there is considerable economic and psychosocial morbidity associated with primary immunodeficiency diseases (PID). Also, the cost of a late diagnosis frequently results in a heavy disease burden on the patient. The objective of this study was to collect and analyze data on patients with PID in the state of Guanajuato in Mexico, to indirectly estimate the burden of the disease.MethodsAn observational, longitudinal, and comparative study was conducted. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 23 publications
7
17
1
2
Order By: Relevance
“…CVID followed by selective IgA deficiency, deficiency of specific IgG antibody and agammaglobulinemia were the prevalent phenotypes. These data are strongly supported by previous reports not only from registries in Latin American countries (6) and Europe (14) but also from reference center hospitals in Cairo, Egypt (9), and Guanajuato, Mexico (10). In Brazil, current data on PID characteristics are scarce.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…CVID followed by selective IgA deficiency, deficiency of specific IgG antibody and agammaglobulinemia were the prevalent phenotypes. These data are strongly supported by previous reports not only from registries in Latin American countries (6) and Europe (14) but also from reference center hospitals in Cairo, Egypt (9), and Guanajuato, Mexico (10). In Brazil, current data on PID characteristics are scarce.…”
Section: Discussionsupporting
confidence: 79%
“…The ratio varied according to the characteristics of the study population, reference centers, or country registers. Normally, males were more prevalent than females (9)(10)(11)(12). The number of patients ≤17 years old was similar to the number of adults.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Many patients with PAD have considerable issues with their physical health which, together with unemployment, have been shown to contribute significantly to a reduced quality of life (QoL). In addition, patients with PAD also experience significant psychosocial and economic distress [12]. It has been widely documented that patients with PAD have reduced perceived health and poorer QoL than healthy matched controls [13].…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing concern regarding costs of medical assistance for patients with different chronic diseases, including primary immunodeficiencies (PID) , which are not so rare and often underdiagnosed. In PID, several studies have shown that costs are often associated with delayed diagnosis .…”
mentioning
confidence: 99%